Regeneration and resource utilization method of catalytic cracking waste catalyst

By adsorbing organic matter and introducing modified metal elements, low-dehydrogenation-active composite oxides are formed, which solves the problem of increased dehydrogenation activity caused by nickel in the catalytic cracking waste catalyst, and improves the activity stability of the catalyst and the resource utilization of waste catalysts.

CN119909770APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311427385.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The high content of nickel in the spent catalyst of catalytic cracking leads to an increase in dehydrogenation activity, affecting the stability of the catalyst and product distribution.

Method used

By contacting the catalytic cracking waste catalyst with organic matter that is not easily soluble in water, adsorbs the organic matter, contacting it with the compound dispersion of the modified metal element, metal elements, such as zirconium, titanium, rare earth and manganese, to form a low-dehydrogenated active composite oxide, and drying and calculating under an inert atmosphere, a regeneration catalyst that inhibits dehydrogenation activity is obtained.

Benefits of technology

It effectively reduces the dehydrogenation activity of nickel in the catalyst, improves the activity stability of the catalyst, and realizes the resource utilization of waste catalysts. It is suitable for start-up agents or supplements for catalytic cracking devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004522626790000081
    Figure BDA0004522626790000081
  • Figure BDA0004522626790000111
    Figure BDA0004522626790000111
  • Figure BDA0004522626790000121
    Figure BDA0004522626790000121
Patent Text Reader

Abstract

The invention belongs to the technical field of environmental protection, and relates to a catalytic cracking waste catalyst regeneration and resource utilization method, which comprises: (1) contacting a catalytic cracking waste catalyst raw material with a water-insoluble organic matter; (2) the waste catalyst adsorbing the organic matter is in contact with the compound dispersion liquid of the modified metal element; and (3) drying and roasting the waste catalyst into which the metal elements are introduced in an inert atmosphere. The obtained regenerated catalyst is used as a starting agent or a supplementing agent of a catalytic cracking device. The method does not need to deeply remove polluted metals, and can reduce the dehydrogenation activity of the waste catalyst used as the starting agent in the catalytic cracking reaction by using a relatively low amount of modified metals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to environmental protection and relates to a method for regenerating and resource-utilizing a catalytic cracking waste catalyst for passivating polluted metals. Background Art

[0002] Since the operation of the first industrial fluid catalytic cracking unit in 1942, catalytic cracking has developed into a core process in refineries, the most important secondary process, and an important means to increase the depth of crude oil processing and the yield of light oil. As crude oil becomes heavier and inferior, FCC catalysts are more susceptible to coking, poisoning and hydrothermal deactivation. In order to meet the needs of the unit and maintain the catalytic cracking performance of the catalyst, it is necessary to regularly unload part of the waste catalyst (i.e., FCC balance) and replenish fresh catalyst. Major domestic refineries produce a large amount of FCC waste catalyst every year. Underground burial is a relatively easy way to treat waste catalysts, but it not only wastes resources but also pollutes the environment. Therefore, it is urgent to study the regeneration and reuse of FCC waste catalysts.

[0003] Since residual oil feed usually contains pollutant metals such as Ni, V, Fe, Na, and Ca, heavy metals such as nickel and vanadium in the feed oil are continuously deposited on the catalyst surface during the use of catalytic cracking catalysts, causing certain poisoning effects on the catalysts. For example, Ni can induce dehydrogenation and significantly increase the yield of H2 and coke.

[0004] The nickel content in catalytic cracking waste is high. If it is used directly as a start-up agent or supplement, it will cause high hydrogen and coke yields. Therefore, the waste agent needs to be regenerated. When it is used as a start-up agent and supplement, it is more conducive to the stable operation of the device and the optimization of product distribution. The regeneration treatment of FCC equilibrium catalyst has been reported at home and abroad, mainly including acid washing, high-intensity magnetic separation (referred to as magnetic separation or magnetic separation), oxidation-chlorination-sulfurization, etc. Magnetic separation mainly uses magnetic force to distinguish the high-nickel iron and low-nickel iron particles in the balance agent, which consumes a lot of energy and has low separation efficiency; acid washing and alkali washing are effective for the removal of vanadium, but inorganic acids and alkalis have basically no effective removal of nickel, and organic acids can only remove up to 30% of nickel; oxidation-chlorination-sulfurization, such as the Demet method in the United States, uses gases such as H2S and HCl, and the demetallization effect can reach more than 70%, but the technical requirements are high. The existing acid washing and alkali washing demetallization processes often have limited nickel removal effects, and are easy to destroy the molecular sieve crystals, which is not conducive to stable activity. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for inhibiting the dehydrogenation activity of spent catalytic cracking catalyst (also called fluidized catalytic cracking (FCC) balancing agent, referred to as balancing agent).

[0006] Another technical problem to be solved by the present invention is to provide a method for resource utilization of the catalyst obtained by the method.

[0007] The present invention provides a method for treating a catalytic cracking waste catalyst to inhibit dehydrogenation activity, the method comprising:

[0008] A catalytic cracking waste catalyst raw material is contacted with an organic substance to obtain a waste catalyst adsorbing organic substances; the organic substances are organic substances that are not easily soluble in water, and in the waste catalyst adsorbing organic substances, the content of the organic substances (or adsorption amount) is more than 10% by volume of the water droplet pore volume of the catalytic cracking waste catalyst raw material, for example, 10-95% by volume or 10% to 80% by volume; the catalytic cracking catalyst raw material is a catalytic cracking waste catalyst and / or a treated catalytic cracking waste catalyst; during the contact, the organic substances are in a liquid or gaseous state, preferably in a gaseous state;

[0009] The organic matter-adsorbed waste catalyst is contacted with a dispersion of a modified metal element compound to obtain a waste catalyst into which a metal element is introduced; the modified metal element is a metal element that can form a low dehydrogenation activity composite oxide with nickel, such as one or more of zirconium, titanium, rare earth and manganese;

[0010] The waste catalyst introduced with the metal element is dried and calcined in an inert atmosphere to obtain a treated catalyst or a regenerated catalyst.

[0011] According to the method for treating a catalytic cracking waste catalyst to inhibit dehydrogenation activity as described in any of the above technical solutions, the catalytic cracking waste catalyst is a catalytic cracking balance agent discharged from a catalytic cracking unit.

[0012] The catalytic cracking spent catalyst is directly or after being treated as the catalytic cracking spent catalyst raw material for the contact with the organic matter that is not easily soluble in water.

[0013] According to the method for treating a catalytic cracking waste catalyst for inhibiting dehydrogenation activity as described in any of the above technical solutions, the treated catalytic cracking waste catalyst may be a first waste catalyst obtained by subjecting the catalytic cracking waste catalyst to a first treatment and / or a second waste catalyst obtained by subjecting the catalytic cracking waste catalyst to a second treatment. For example, it may be a first waste catalyst obtained only by subjecting the catalytic cracking waste catalyst to a first treatment, a second waste catalyst obtained only by subjecting the catalytic cracking waste catalyst to a second treatment, or a second waste catalyst obtained by subjecting the first treatment and the second treatment.

[0014] According to the treatment method for inhibiting dehydrogenation activity of catalytic cracking waste catalyst described in any of the above technical solutions, the first treatment is to treat the catalytic cracking waste catalyst with one or more methods selected from the group consisting of activation, chemical demetallization treatment and physical treatment; the activation is one or more selected from the group consisting of weak acid washing, ammonium exchange, phosphorus treatment and rare earth exchange treatment; the physical treatment is one or more selected from the group consisting of magnetic separation and air separation; the secondary selection is to separate particles with high content of magnetic metals such as nickel and iron from the catalytic cracking waste catalyst by magnetic separation; the air separation is to separate fine powder from the catalytic cracking waste catalyst by wind blowing; through the first treatment, a first waste catalyst is obtained.

[0015] According to the method for treating catalytic cracking waste catalyst to inhibit dehydrogenation activity as described in any of the above technical solutions, the second treatment is to vacuum treat the catalytic cracking waste catalyst and / or the first waste catalyst, and the vacuum treatment is to evacuate the catalytic cracking waste catalyst and / or the first waste catalyst to a certain vacuum pressure; to obtain a second waste catalyst.

[0016] According to the method for treating catalytic cracking waste catalyst to inhibit dehydrogenation activity described in the above technical solution, in the second treatment: the certain vacuum pressure (absolute pressure) is 1Pa to 10 -5 paFor example 0.1Pa~10 -5 pa, preferably 10 -2 Pa~10 -4 pa; the vacuum treatment time is, for example, 10 min to 120 min, preferably 20 min to 50 min; the vacuum treatment discharges the placeholder gas in the waste catalyst to facilitate the subsequent adsorption of organic gas and the introduction of metal into the appropriate position.

[0017] According to the present invention, the catalytic cracking waste catalyst is also called FCC waste catalyst, which is a balance agent produced in the catalytic cracking process. The catalytic cracking waste catalyst contains nickel, and the nickel weight content can be higher than 2000ppm. In the catalytic cracking process, the nickel in the oil product is deposited on the catalyst to form deposited nickel. Nickel promotes undesirable reactions in the catalytic cracking process, such as promoting dehydrogenation reactions. Catalytic cracking waste catalysts with a nickel weight content higher than 3000ppm, for example, catalytic cracking waste catalysts with a nickel content of 3500 to 8000ppm by weight are generally called high-nickel balance agents or high-nickel catalytic cracking waste catalysts. The method provided by the present invention can be used for the reprocessing and resource utilization of catalytic cracking balance agents with high nickel content.

[0018] In one embodiment, the nickel content by weight in the catalytic cracking waste catalyst is less than 9000 ppm, for example, 2000-9000 ppm or 3500-8000 ppm.

[0019] According to the treatment method for inhibiting dehydrogenation activity of catalytic cracking waste catalyst described in any of the above technical solutions, the catalytic cracking waste catalyst may also contain vanadium, and there is no special requirement for the vanadium content. For example, the vanadium weight content may be above 500ppm, for example, 500-8000ppm or 500-6000ppm. In the catalytic cracking process, vanadium in the oil product will be deposited on the catalyst to form deposited vanadium, and vanadium will destroy the structure of the molecular sieve in the catalyst. The method provided by the present invention is also effective in inhibiting the toxicity of vanadium in the balance agent.

[0020] According to the method for treating the catalytic cracking waste catalyst to inhibit the dehydrogenation activity described in any of the above technical solutions, the catalytic cracking waste catalyst can be a catalytic cracking waste catalyst produced by a catalytic cracking unit or a catalytic cracking unit. Generally, the catalytic cracking waste catalyst contains a molecular sieve, and the molecular sieve is, for example, one or more of a Y-type molecular sieve, an MFI structure molecular sieve, and a β molecular sieve.

[0021] According to the method for treating catalytic cracking waste catalyst to inhibit dehydrogenation activity as described in any of the above technical solutions, the catalytic cracking waste catalyst can be directly treated as the catalytic cracking waste catalyst raw material, and demetallization treatment is not required. The treatment can be directly used to reduce the pollution of active nickel and also to fix vanadium, which is simple and convenient.

[0022] According to the method for treating catalytic cracking waste catalyst to inhibit dehydrogenation activity as described in any of the above technical solutions, the V content in the catalytic cracking waste catalyst raw material is preferably not more than 6000 ppm, and the nickel weight content is less than 9000 ppm, for example, 3500-8000 ppm.

[0023] In one embodiment, the metal contents in the catalytic cracking spent catalyst raw material are: Ni content does not exceed 9000 ppm by weight, for example, 2000-9000 ppm or 4000-9000 ppm or 3500-8000 ppm, V content does not exceed 8000 ppm by weight, for example, 500-6000 ppm or 3000-8000 ppm.

[0024] Preferably, the metal contents in the first treated catalytic cracking waste catalyst, i.e. the first waste catalyst, are as follows: Ni content does not exceed 9000 ppm by weight, for example, 4000-9000 ppm, and V content does not exceed 8000 ppm by weight, for example, 3000-8000 ppm or 500-6000 ppm.

[0025] According to the method for treating catalytic cracking waste catalyst to inhibit dehydrogenation activity as described in any of the above technical solutions, the weight content of nickel in the catalytic cracking waste catalyst is 500-6000 ppm.

[0026] According to the method for treating catalytic cracking waste catalyst to inhibit dehydrogenation activity as described in any of the above technical schemes, wherein the contacting of the catalytic cracking waste catalyst raw material with the organic matter that is not easily soluble in water in step (1) is: contacting the catalytic cracking waste catalyst raw material with the organic matter gas that is not easily soluble in water, preferably contacting with the organic matter gas that is not easily soluble in water under vacuum conditions, the content of organic matter in the waste catalyst adsorbing organic matter is 20 volume % to 95 volume % of the water droplet pore volume of the catalytic cracking waste catalyst raw material, for example, 20 to 80 volume % or 30 to 60 volume %, wherein the volume of the organic matter is the volume under standard conditions; the contact temperature can be 15 to 60°C.

[0027] In one embodiment, in step (1), the catalytic cracking spent catalyst raw material is contacted with the organic matter that is not easily soluble in water by placing the second spent catalyst under a pressure (absolute pressure) of 0.1 Pa to 10 -5 pa, preferably 10 -2 Pa~10 -4 In a container under pa, organic matter gas that is not easily soluble in water is sucked in through the vacuum degree of the container, thereby contacting with the second waste catalyst in the container, and the second waste catalyst adsorbs the organic matter that is not easily soluble in water until the content of organic matter in the obtained waste catalyst with organic matter meets the requirement.

[0028] According to the method for treating catalytic cracking waste catalyst to inhibit dehydrogenation activity as described in any of the above technical solutions, the organic matter is an organic matter having a boiling point greater than 100°C and not exceeding 250°C at 1 atm, and the boiling point of the organic matter at 1 atm is, for example, 110°C to 220°C, preferably 120°C to 200°C.

[0029] According to the method for treating catalytic cracking waste catalyst to inhibit dehydrogenation activity described in any of the above technical solutions, in one embodiment, the organic matter that is not easily soluble in water is one or more of hydrocarbons or organic matter containing S, P or N. The organic matter that is not easily soluble in water includes, but is not limited to, one or more of benzene, toluene, xylene, trimethylbenzene, trimethylphosphine, picoline, and collidine.

[0030] According to the treatment method for inhibiting the dehydrogenation activity of catalytic cracking waste catalysts described in any of the above technical solutions, the waste catalyst adsorbing organic matter is contacted with a dispersion of a compound of a modified metal element by equal volume impregnation, excess impregnation, or spraying. The contact can be performed once or multiple times. When performed multiple times, a second drying is performed after the contact, and then the next contact is performed. The second drying is slow drying. The drying (referred to as the first drying) in step (3) is slow drying. In one embodiment, the slow drying is performed by a programmed temperature drying method. For example, the heating rate of the programmed temperature drying is 0.1 to 3°C / min, and the highest drying temperature does not exceed 180°C. The programmed temperature can usually be started from 60°C. In one embodiment, the temperature is increased from 60°C to 100°C at a rate not exceeding 1°C / min, such as 0.3-0.8°C / min, and maintained at 100°C for 0.2-1 hour, then increased to 150°C at a rate of 1-2°C, and maintained at 150°C for 0.2-2 hours. The drying is carried out under an inert atmosphere, such as a nitrogen atmosphere, and the volatile gas generated by the drying can be removed in time by flowing the atmosphere.

[0031] According to the treatment method for suppressing the dehydrogenation activity of the catalytic cracking waste catalyst described in any of the above technical solutions, the compound of the modified metal element is a salt of the modified metal element, and the dispersion is an aqueous solution of the salt of the modified metal element. In one embodiment, the waste catalyst adsorbing organic matter is contacted with the dispersion of the compound of the modified metal element, so that the modified metal element, such as one or more of zirconium, titanium, rare earth and manganese, is loaded into the catalytic cracking waste catalyst by impregnation. Further, multiple impregnation methods can be used to increase the surface impregnation amount. The modified metal salt is, for example, one or more of the nitrate, chloride, sulfate, and metal acid salt of the modified metal, such as one or more of zirconium chloride, titanium chloride, rare earth chloride, manganese chloride, zirconate, titanate, manganate, zirconium nitrate, titanium nitrate, rare earth nitrate, and manganese nitrate.

[0032] According to the method for treating catalytic cracking waste catalyst to inhibit dehydrogenation activity as described in any of the above technical solutions, the drying and calcination in step (3) are drying and calcination in an inert atmosphere, the calcination temperature is 350-650°C, the calcination time is 0.2-5h, and the drying temperature can be 60-180°C.

[0033] The product obtained by the treatment method for inhibiting the dehydrogenation activity of the catalytic cracking waste catalyst of the present invention is called a regenerated catalyst. In one embodiment, the content of the modified metal element in terms of element accounts for 0.1% to 5% by weight of the total weight of the regenerated catalyst on a dry basis. Preferably, the content of the modified metal element in terms of element accounts for 0.3% to 4% by weight of the total weight of the regenerated catalyst on a dry basis, such as 0.5% to 3% by weight. The present invention can have a better effect at a lower modified metal content. In addition, it can also prevent excessive loaded metal from entering the catalyst and inducing other side reactions.

[0034] The regenerated catalyst obtained by the method described in any of the above technical solutions.

[0035] The regenerated catalyst described in the above technical solution is used as a start-up agent or supplement for a catalytic cracking unit.

[0036] The method for treating the catalytic cracking waste catalyst to inhibit the dehydrogenation activity provided by the present invention can reduce the dehydrogenation activity of nickel in the catalytic cracking waste catalyst and improve the activity stability of the treated catalyst. The obtained regenerated catalyst can be used as a start-up agent or supplement for catalytic cracking or catalytic cracking, and can realize resource utilization of the waste catalyst. Furthermore, the acidity of the catalyst can be adjusted by using rare earth compounds and / or phosphorus compounds, so that the performance of the catalytic cracking waste catalyst can be restored.

[0037] The regenerated catalyst obtained by the treatment method for inhibiting the dehydrogenation activity of the catalytic cracking waste catalyst provided by the present invention can effectively reduce the hydrogen yield of hydrocarbon oil conversion and the hydrogen-methane ratio compared with the catalytic cracking waste catalyst, and the dry gas yield can be lower, and the activity stability of the regenerated catalyst is better. Preferably, it can have a higher gasoline yield and / or a higher liquefied gas yield.

[0038] The method for treating the catalytic cracking waste catalyst to inhibit the dehydrogenation activity provided by the present invention can be used for treating the catalytic cracking waste catalyst produced by the FCC, RFCC or DCC catalytic cracking process. The treated catalyst obtained after the treatment, or the regenerated catalyst, can be used as a catalyst or supplement for the start-up of a catalytic cracking unit. For example, it is used as a start-up agent when the catalytic cracking unit is started up, or as a supplement that requires a large dose of replenishment when the unit reserves are seriously insufficient. Compared with the balancing agent that has not been treated, it can make the dry gas and coke yields lower during the stable operation of the unit, and the molar ratio of hydrogen to methane in the product lower. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a schematic diagram of the impregnation device used in the present invention.

[0040] 1 of which is a vacuum treatment reactor

[0041] 2 is the organic matter storage tank

[0042] 3 is the vacuum pump

[0043] 4 is the outlet valve of the organic liquid storage tank, called valve B

[0044] 5 is a vacuum valve, called valve A

[0045] 6 is the vent valve DETAILED DESCRIPTION

[0046] According to the present invention, in one embodiment, the processing method of the present invention comprises:

[0047] (S1) performing a first treatment on the spent catalytic cracking catalyst to obtain a first spent catalyst;

[0048] (S2) The first waste catalyst is placed at an absolute pressure of 0.1 Pa to 10 -5 pa, and vacuum treatment is performed to obtain a second waste catalyst;

[0049] (S3) adsorbing organic matter on the second waste catalyst under vacuum conditions, wherein the organic matter is xylene, trimethylbenzene or picoline, and the adsorption amount is 20% to 80% of the total volume calculated by the water droplet pore volume;

[0050] (S4) using a metal lanthanum and / or manganese salt solution for immersion treatment or spray treatment;

[0051] (S5) Slowly drying and calcining the product obtained in S4 under an inert atmosphere.

[0052] According to the method for treating catalytic cracking waste catalyst to inhibit dehydrogenation activity described in the above embodiment, in step (S1), the V content in the first waste catalyst does not exceed 6000 ppm, and the nickel weight content is less than 9000 ppm, for example, 3500-8000 ppm.

[0053] In step (S3), in the waste catalyst adsorbing organic matter, the content of the organic matter (or the adsorption amount of the organic matter) is 20% to 80% by volume of the water droplet pore volume of the catalytic cracking waste catalyst raw material; preferably 20% to 75%.

[0054] In step (S4), the impregnation method is saturated impregnation or excessive impregnation, and the impregnation treatment time is, for example, more than 5 minutes, for example, 10 to 60 minutes. Generally, the impregnation process does not include the step of adding a precipitant to precipitate the modified metal.

[0055] According to the method for treating catalytic cracking waste catalyst to inhibit dehydrogenation activity provided by the present invention, the catalytic cracking waste catalyst can also be used as catalytic cracking waste catalyst raw material for the organic matter treatment after pretreatment.

[0056] The pretreatment may include a first treatment and / or a second treatment. The first treatment may be an activation and / or demetallization treatment and / or a particle size adjustment treatment. The demetallization treatment may be magnetic separation, chemical demetallization such as wet and pyrometallization treatment, and chemical demetallization may further include but not limited to one or more of chlorination-sulfurization pyrometallization, organic acid demetallization, inorganic acid demetallization, and alkaline demetallization. These demetallization methods may adopt existing methods. The demetallization treatment may be a shallow demetallization treatment, so that the nickel content in the catalyst after demetallization is above 2000ppm by weight, such as 2000-9000ppm by weight. The shallow demetallization treatment may reduce the cost of the demetallization treatment, reduce the damage to the catalyst structure, and help maintain the activity of the catalyst. The activation may be, for example, weak acid washing, ammonium exchange, phosphorus treatment, and rare earth exchange treatment. The particle size adjustment treatment may, for example, be a gas separation method or a screening method to separate the fine powder in the catalytic cracking waste catalyst so that the particle size of the product meets the requirements of catalytic cracking.

[0057] The present invention will be further described in the following examples, but the present invention is not limited thereto.

[0058] The catalytic cracking waste catalyst used in the embodiment is a balance agent of an oil refinery, denoted as ECat-A, containing a Y-type molecular sieve, and its basic chemical composition is shown in Table 1. The chemical composition is determined by X-ray fluorescence (XRF), and the specific steps refer to ASTM D7085-04 (2010) Standard Guide for Determination of Chemical Elements in Fluid Catalytic Cracking Catalysts - Guide for Determination by X-ray Fluorescence Spectrometry.

[0059] The toluene used was o-xylene, analytical grade, purchased from Sinopharm Group Reagent Company.

[0060] Benzene, analytical grade, was purchased from Sinopharm Group Reagent Company.

[0061] Lanthanum chloride tetrahydrate, analytical grade, was purchased from Sinopharm Group Reagent Company.

[0062] Manganese chloride, analytical grade, was purchased from Sinopharm Group Reagent Company.

[0063] Micro-reaction activity index: The standard method of RIPP92-90 (see "Petrochemical Analysis Method" (RIPP Test Method) edited by Yang Cuiding et al., Science Press, published in 1990) was used to evaluate the light oil micro-reaction activity of the sample. The catalyst loading was 5.0 g, the reaction temperature was 460°C, the feed oil was straight-run light diesel with a distillation range of 235-337°C, and the product composition was analyzed by gas chromatography. The light oil micro-reaction activity MA was calculated based on the product composition.

[0064] Water drop method pore volume measurement method: in accordance with NB / SH / T 0955-2017.

[0065] In the examples and comparative examples, the temperature not explicitly stated was the room temperature of 26°C.

[0066] In the embodiment, the treatment device used is a 30 ml vacuum treatment reactor, which is a sealable quartz chamber, connected to a vacuum pump by a connecting valve (called valve A), another connecting valve (called valve B) connected to a xylene storage pipe, and also connected to a vent valve (called valve C). The flow diagram is shown in FIG. Figure 1 shown.

[0067] Table 1

[0068]

[0069] Example 1

[0070] 10 g of ECat-A (on a dry basis) was placed in the 30 ml vacuum treatment reactor. After closing the vent valve and valve B, valve A was opened and the vacuum pump was turned on to perform vacuum treatment. When the absolute pressure reached 10 -3 pa, close valve A and then slowly open valve B. When the xylene in the xylene storage tank is reduced by about 2.0 ml by volatilization under vacuum, close valve B to obtain a catalyst with adsorbed xylene. The volume of adsorbed xylene is about 60% by volume of the pore volume of the ECat-A water drop method.

[0071] The catalyst that had absorbed xylene was placed in 10 ml of lanthanum chloride solution with a concentration of 5 wt% in terms of lanthanum oxide (La2O3) and manually stirred for immersion for 20 minutes. It was then filtered and slowly dried in a nitrogen atmosphere (placed in an oven at 60°C, and the temperature was set to rise from 60°C to 100°C over 60 minutes, and kept at 100°C for 30 minutes to fully dry, and then heated to 150°C over 30 minutes, and kept at 150°C for 30 minutes (the gas was removed in time). The temperature was then raised to 400°C and kept for 30 minutes. A catalytic cracking catalyst C1 with a lanthanum oxide loading of about 2.0 wt% was obtained.

[0072] Example 2

[0073] Place 10 g of ECat-A (dry basis) in a 30 ml vacuum treatment reactor, close the vent valve and valve B, open valve A, turn on the vacuum pump, and perform vacuum treatment. When the absolute pressure reaches 10 -3 When pa, valve A is closed, and then valve B is slowly opened. When the toluene in the toluene storage tank is reduced by about 2.1 ml by volatilization under vacuum, valve B is closed to obtain a catalyst after toluene adsorption, wherein the amount of toluene adsorbed is about 60% by volume of the pore volume of ECat-A (water drop method).

[0074] The catalyst that had absorbed toluene was placed in 10 ml of a lanthanum chloride solution with a concentration of 5% by weight based on lanthanum oxide, and was manually stirred and immersed for 20 minutes. It was then filtered and then slowly dried in a nitrogen atmosphere (the temperature was programmed to rise from 60°C to 100°C over 60 minutes, and kept at 100°C for 30 minutes to fully dry, and then heated to 120°C over 30 minutes, and kept at 120°C for 30 minutes (the gas was removed in time). A catalytic cracking catalyst C2 with a lanthanum oxide loading of about 2.1% by weight was obtained.

[0075] Example 3

[0076] Place 10 g of ECat-A (dry basis) in a 30 ml vacuum treatment reactor, close the vent valve and valve B, open valve head A, turn on the vacuum pump, and perform vacuum treatment. When the absolute vacuum pressure reaches 10 -3 When the temperature reaches 1000 pa, valve A is closed, and then valve B is slowly opened. When the xylene in the xylene storage tank is reduced by about 3.0 ml by volatilization under vacuum, valve B is closed. A catalyst having adsorbed xylene is obtained, wherein the adsorption amount of xylene is 90% by volume of the pore volume of ECat-A (water drop method).

[0077] The catalyst that had absorbed xylene was placed in 10 ml of a lanthanum chloride solution with a concentration of 5% by weight based on lanthanum oxide, and was manually stirred and immersed for 20 minutes. It was then filtered and then slowly dried in a nitrogen atmosphere (the temperature was programmed to rise from 60°C to 100°C over 60 minutes, and kept at 100°C for 30 minutes to fully dry, and then heated to 150°C over 30 minutes, and kept at 150°C for 30 minutes (the gas was removed in time). Then the temperature was raised to 400°C and kept for 30 minutes. A catalytic cracking catalyst C3 with a lanthanum oxide loading of about 0.6% by weight was obtained.

[0078] Example 4

[0079] The catalyst obtained by the method of Example 1 after adsorbing xylene was placed in 10 ml of a manganese chloride solution with a concentration of 5 wt% in terms of manganese oxide (MnO) and manually stirred for 20 min. It was then filtered and then slowly dried in a nitrogen atmosphere (the temperature was set to rise from 60°C to 100°C over 60 min, and kept at 100°C for 30 min to fully dry, and then raised to 150°C over 30 min, and kept at 150°C for 30 min (the gas was removed in time). Then the temperature was raised to 400°C and kept for 30 min. A catalytic cracking catalyst C4 with a manganese oxide (MnO) loading of about 2.3 wt% was obtained.

[0080] Example 5

[0081] 2.0 ml of xylene was added dropwise into 10 g of ECat-A (dry basis) while being continuously stirred to obtain a catalytic cracking catalyst that adsorbed xylene.

[0082] The catalytic cracking catalyst that had absorbed xylene was placed in 10 ml of a lanthanum chloride solution with a concentration of 5 wt% in terms of lanthanum oxide (La2O3) and manually stirred for immersion for 20 minutes. It was then filtered and slowly dried in a nitrogen atmosphere (placed in an oven at 60°C, and the temperature was set to rise from 60°C to 100°C over 60 minutes, and kept at 100°C for 30 minutes to fully dry. Then the temperature was raised to 150°C over 30 minutes, and kept at 150°C for 30 minutes (the gas was removed in time). The temperature was then raised to 400°C and kept for 30 minutes. A catalytic cracking catalyst C5 with a lanthanum oxide loading of 3.1 wt% was obtained.

[0083] Comparative Example 1

[0084] 10g of ECat-A was placed in 10ml of lanthanum chloride solution with a concentration of 5% by weight of lanthanum oxide (La2O3) and manually stirred for immersion for 20 minutes, then filtered and slowly dried in a nitrogen atmosphere (placed in an oven at 60°C, set the temperature program to rise from 60°C to 100°C after 60 minutes, kept at 100°C for 30 minutes to fully dry, then heated to 150°C after 30 minutes, and kept at 150°C for 30 minutes (the gas was removed in time). Then the temperature was raised to 400°C and kept for 30 minutes. A catalytic cracking catalyst D2 with a lanthanum oxide loading of about 4.1% by weight was obtained.

[0085] Comparative Example 2

[0086] After vacuum treatment and xylene adsorption on ECat-A as in Example 1, all the ECat-A after xylene adsorption was placed in 10 ml of lanthanum chloride solution with a concentration of 5% by weight based on lanthanum oxide, and then, under manual stirring, ammonia water was added dropwise to adjust the pH to 10, and then further stirred and filtered, and then slowly dried under a nitrogen atmosphere (set the program temperature to rise from 60°C to 100°C after 60min and keep warm for 30min to fully dry, and then rise to 150°C in 30min and keep warm for 30min (the gas was promptly removed). Then the temperature was raised to 400°C and kept warm for 30min. A catalytic cracking catalyst D3 with a lanthanum oxide loading of about 2.5% by mass was obtained.

[0087] Embodiments 6 to 10

[0088] This example illustrates the metal resistance of the heavy oil cracking catalyst provided by the present invention.

[0089] Samples C1 to C5 were evaluated using an ACE fluidized bed apparatus. The ACE-evaluated crude oil properties are shown in Table 2, and the evaluation conditions and results are shown in Table 3.

[0090] Comparative Examples 3 to 5

[0091] This comparative example illustrates the metal resistance of the spent catalyst ECat-A and the comparative catalyst provided by the present invention.

[0092] Catalysts ECat-A, D2, and D3 were evaluated using an ACE fluidized bed apparatus. The ACE evaluated feedstock oil properties are shown in Table 2, and the evaluation conditions and results are shown in Table 3.

[0093] Table 2

[0094]

[0095]

[0096] As can be seen from Table 3, the regenerated catalyst obtained by the high-nickel catalytic cracking balance agent treatment method provided by the present invention is applied to the start-up catalyst and supplement of the catalytic cracking unit. Compared with the unregenerated ECat-A catalyst, it has a more stable activity and a significantly lower hydrogen yield, and can greatly reduce the hydrogen-methane ratio. Preferably, a lower coke yield can be achieved at a higher heavy oil conversion rate.

[0097] Stability evaluation:

[0098] The catalysts and comparative agents prepared according to the methods of Examples 1 to 5 were aged at 780°C in a 100% by volume water vapor atmosphere for 4 hours, and the micro-reaction activity was evaluated. The results are shown in Table 3. It can be seen that the micro-activity reduction ratio of the catalyst of the present invention after aging is small, and the activity stability is high. The activity stability is significantly higher than the existing method of regenerating catalytic cracking catalytic waste catalyst with acid, while the acid modification method in the prior art can only improve the apparent activity, which has a destructive effect on the activity after aging, and may even be lower than the stable activity of the balance agent without any treatment.

Claims

1. A method for treating a catalytic cracking waste catalyst to inhibit dehydrogenation activity, the method comprising: (1) A catalytic cracking waste catalyst raw material is contacted with an organic matter that is not easily soluble in water to obtain a waste catalyst adsorbing the organic matter; in the waste catalyst adsorbing the organic matter, the content of the organic matter that is not easily soluble in water is more than 10% by volume of the water droplet pore volume of the catalytic cracking waste catalyst raw material; the catalytic cracking catalyst raw material is a catalytic cracking waste catalyst and / or a treated catalytic cracking waste catalyst; during the contacting, the organic matter that is not easily soluble in water is in a liquid or gaseous state; (2) the waste catalyst adsorbing organic matter is contacted with a dispersion of a compound of a modified metal element to obtain a waste catalyst into which a metal element is introduced; the modified metal element is a metal element that can form a composite oxide with low dehydrogenation activity with nickel; (3) The waste catalyst introduced with the metal element is dried and calcined in an inert atmosphere to obtain a treated catalyst.

2. The method according to claim 1, characterized in that The catalytic cracking waste catalyst is a catalytic cracking balance agent discharged from a catalytic cracking unit; The treated catalytic cracking spent catalyst is a first spent catalyst obtained by subjecting the catalytic cracking spent catalyst to the first treatment and / or a second spent catalyst obtained by subjecting the catalytic cracking spent catalyst to the second treatment; The first treatment is to treat the spent catalytic cracking catalyst by one or more methods selected from activation, chemical demetallization and physical treatment; through the first treatment, a first spent catalyst is obtained; The second treatment is to subject the catalytic cracking waste catalyst and / or the first waste catalyst to vacuum treatment, wherein the vacuum treatment is to evacuate the catalytic cracking waste catalyst and / or the first waste catalyst to a certain vacuum pressure to obtain a second waste catalyst; The catalytic cracking waste catalyst raw material has a V content of no more than 6000 ppm and a nickel weight content of less than 9000 ppm; In the first waste catalyst, the V content does not exceed 6000 ppm, and the nickel weight content is less than 9000 ppm.

3. The method according to claim 1 or 2, characterized in that: The nickel content in the catalytic cracking waste catalyst is 500 to 6000 ppm by weight.

4. The method according to claim 2, characterized in that: The second treatment: the certain vacuum pressure is 10 - 5 Pa~0.1Pa absolute pressure, preferably 10 -4 ~10 -2 Pa absolute pressure; the vacuum treatment time is, for example, 10 min to 120 min, such as 20 min to 50 min.

5. The method according to claim 1, characterized in that In step (1), the catalytic cracking waste catalyst raw material is contacted with the organic matter that is not soluble in water by contacting the catalytic cracking waste catalyst raw material with the organic matter gas that is not soluble in water, preferably contacting the organic matter gas that is not soluble in water under vacuum conditions, wherein the content of the organic matter that is not soluble in water in the waste catalyst that adsorbs the organic matter is 10 volume % to 95 volume % of the water droplet pore volume of the catalytic cracking waste catalyst raw material, wherein the volume of the organic matter that is not soluble in water refers to the volume under standard conditions.

6. The method according to claim 1, 4 or 5, characterized in that: In the waste catalyst adsorbing organic matter, the content of the organic matter that is not easily soluble in water is 20 volume % to 80 volume % of the water droplet pore volume of the catalytic cracking waste catalyst raw material.

7. The method according to claim 1, characterized in that The organic matter that is not easily soluble in water is an organic matter having a boiling point greater than 100° C. and not exceeding 250° C. at 1 atm; In one embodiment, the organic matter that is not easily soluble in water is one or more of hydrocarbons or organic matter containing S, P or N; the organic matter that is not easily soluble in water is, for example, one or more of benzene, toluene, xylene, trimethylbenzene, trimethylphosphine, methylpyridine, and trimethylpyridine.

8. The method according to claim 1, characterized in that The waste catalyst adsorbing organic matter is contacted with a dispersion of a compound of a modified metal element by equal volume impregnation, excess impregnation, or spraying. The contact can be performed once or multiple times. When multiple contacts are performed, a second drying is performed after each contact, and then the next contact is performed. The second drying is slow drying. In one implementation mode, the slow drying is performed by a programmed temperature drying method, and the heating rate of the programmed temperature drying is 0.1 to 3°C / min, and the highest drying temperature does not exceed 180°C.

9. The method according to claim 1 or 8, characterized in that: The modified metal element compound is a salt of the modified metal element, the dispersion is an aqueous solution of the salt of the modified metal element, and the modified metal element is, for example, one or more of zirconium, titanium, rare earth and manganese.

10. The method according to claim 1, characterized in that The drying and calcining in step (3) are carried out under an inert atmosphere, the calcining temperature is 350 to 650° C., the calcining time is 0.2 to 5 hours, and the drying temperature can be 60 to 180° C.

11. A method for treating and utilizing spent catalytic cracking catalyst, comprising: (S1) subjecting the spent catalytic cracking catalyst to a first treatment to obtain a first spent catalyst; (S2) The first waste catalyst is placed at an absolute pressure of 0.1 Pa to 10 -5 pa, and vacuum treatment is performed to obtain a second waste catalyst; (S3) adsorbing organic matter that is not easily soluble in water on the second waste catalyst under vacuum conditions to obtain a waste catalyst adsorbing organic matter; the organic matter that is not easily soluble in water is preferably xylene, trimethylbenzene or picoline; the amount of organic matter that is not easily soluble in water in the waste catalyst adsorbing organic matter is 20 volume % to 80 volume % of the volume of the water droplet pore; (S4) using a metal lanthanum and / or manganese salt solution for immersion treatment or spray treatment; (S5) Slowly drying and calcining the product obtained in S4 under an inert atmosphere.

12. The regenerated catalyst obtained by the method according to any one of claims 1 to 11.

13. Use of the regenerated catalyst according to claim 12 as a start-up agent or supplement for a catalytic cracking unit.